IDENTIFIKASI KESEHATAN MENTAL GURU DI KABUPATEN MADIUN - Widyaningsih, Bernadeta Dhaniswara (Widya Warta, 2014)
The aim of this study was to identify the demographic factors, such as teaching experience, sex, number of children, marital status, and age which affect teachers, especially the way howto deal with problems and mental health which may affect their daily work. The subject of this research was teachers who are already certified and working in Madiun Regency. Thosefactors were measured using Coping Mechanism Scale and Mental Health Scale with multivariate data analysis. The results of the study indicated that the demographic factors(teaching experience, home-to-school distance, the number of children, marital status, and age) of the teachers were correlated a Coping Mechanism and their mental health as indicated by the value of F = 71.340; R2= 0.200, so the effective contribution of this study is 20%. The demographic factors which affect the teachers’ Coping Mechanism and Mental Health include teaching experience, home-to-school distance, number of children, and age of the teachers.